Dying, assisted death and mourning - Kasher, Asa. (Amsterdam ; New York, NY : Rodopi, 2009)
Dying and death are topics of deep humane concern for many people in a variety of circumstances and contexts. However, they are not discussed to any great extent or with sufficient focus in order to gain knowledge and understanding of their major features and aspects. The present volume is an attempt to bridge the undesirable gap between what should be known and understood about dying and death and what is easily accessible. Included in the present volume are chapters arranged in three sections. First, there are chapters on aspects of dying, written by people who have professional experience and.
Are We Barking Up the Wrong Tree? Questioning the Appropriateness of Human Models for Understanding Bereavement as Applied to the Experience of Companion Animal Loss through EuthanasiaSection 3 Mourning; The Saying Hallo Metaphor as Alternative Approach to Death-Related Counselling; Remembering the Dead: Roadside Memorials in Ireland; "Untitled" (Queer Mourning and the Art of Felix Gonzalez-Torres); Contributors.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Death; Euthanasia -- Moral and ethical aspects; Bereavement; Death; Bereavement; Mort; Euthanasie -- Aspect moral; Deuil; deaths; mourning; SOCIAL SCIENCE -- Death & Dying; FAMILY & RELATIONSHIPS -- Death, Grief, Bereavement; Bereavement; Death; Euthanasia -- Moral and ethical aspects